Teacher Feedback Practices, Student Feedback Motivation, and Feedback Behavior: How Are They Associated With Learning Outcomes? - Gan, Zhengdong; An, Zhujun; Liu, Fulan (Frontiers in Psychology, 2021)
In spite of much recent theorizing about teacher provision of feedback, relatively fewer studies look at the dynamic relationships between teacher feedback practices, student feedback experience, and their learning outcomes in higher education settings. To fill this gap, this study looked at 308 university students’ perceived teacher feedback practices and their feedback experiences in an English Studies course context at a key and non-key university, and explored how teacher feedback, student feedback motivation and feedback behavior were associated with students’ course satisfaction and course exam performance. Results showed that students from the key university reported a higher level of teacher feedback use as well as student feedback motivation and behavior. Structural equation modeling (SEM) suggested that in the case of the non-key university, student feedback behavior significantly predicted course satisfaction and course exam results; teacher feedback also indirectly influenced course satisfaction and course exam results. In the case of the key university, while teacher feedback and student feedback behavior each had significant influence on course satisfaction, student feedback behavior showed no direct significant effect on course exam results, and teacher feedback also showed no significant indirect influence on course exam results.